Cover Feature: Immobilization of Perylene‐3, 4, 9, 10‐Tetracarboxylic Dianhydride on Hollow Polysulfone Fibers: Primary Amine Coupling and Fluorescence Reporting (ChemPlusChem 9/2019). Issue 9 (18th July 2019) - Favaretto, Laura; Manoli, Francesco; Zambianchi, Massimo; Bocchi, Letizia; Ventura, Barbara; Manet, Ilse; Melucci, Manuela
Abstract : The cover feature shows how polysulfone hollow fibers can be used as a versatile platform for the adsorption of perylene‐based dyes by means of a wet coating procedure. The immobilized dyes can then react with amino‐functionalized small molecules. The covalent binding process occurring on the fiber surface has been studied by means of fluorescence spectral and lifetime changes. This simple approach has potential applications in biomedical sensing. More details are given in the Full Paper by I. Manet, M. Melucci, and co‐workers on page 1299 in Issue 9, 2019 (DOI: 10.1002/cplu.201800681 ).